Rāingān kānwičhai r̄ưang ʻutsāhakam namtān nai Prathēt Thai - Somphop Mānarangsan, 1950- (Sathāban ʻĒchīasưksā, Čhulālongk̨ōnmahāwitthayālai, 1987)
Study on sugar industry in Thailand; includes statistics.